2021
DOI: 10.1111/jen.12869
|View full text |Cite
|
Sign up to set email alerts
|

The role of insect pollinators in avocado production: A global review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 48 publications
(92 reference statements)
4
38
0
Order By: Relevance
“…Our data shows a unique bee community visiting each of the two crops studied, highlighting that crop species in the tropical mountains likely rely on more specialized assemblages of bees. A recent review of avocado pollination found that stingless bees are as effective as the honey bee at avocado pollination and suggested that the contribution from wild pollinators to avocado pollination may be higher in Central American countries, owing to the co-evolution of pollinators and avocados in Central America, but found that no studies of avocado pollination had yet been conducted in any Central American country 31 . Our study found that 10 of 19 bee species collected from avocado flowers were stingless bee species, and for 7 of those 10 stingless bee species, we observed abundance differences by elevation; all 7 stingless bee species were more frequently observed in the lower elevation zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data shows a unique bee community visiting each of the two crops studied, highlighting that crop species in the tropical mountains likely rely on more specialized assemblages of bees. A recent review of avocado pollination found that stingless bees are as effective as the honey bee at avocado pollination and suggested that the contribution from wild pollinators to avocado pollination may be higher in Central American countries, owing to the co-evolution of pollinators and avocados in Central America, but found that no studies of avocado pollination had yet been conducted in any Central American country 31 . Our study found that 10 of 19 bee species collected from avocado flowers were stingless bee species, and for 7 of those 10 stingless bee species, we observed abundance differences by elevation; all 7 stingless bee species were more frequently observed in the lower elevation zone.…”
Section: Discussionmentioning
confidence: 99%
“…However, if wild honey bee populations decline, then local farmers will have to rely more heavily on native species, particularly the highly abundant social stingless bees (Tribe Meliponini). Wild bee species richness, total bee abundance, functional group diversity, and the abundance of the most effective bee species have all been linked to crop yield, fruit quality and fruit size, however, these relationships have yet to be verified for most tropical crop species 5 , 31 , 33 , 34 . This highlights an urgent need to protect multiple metrics of bee populations, including relative abundances.…”
Section: Discussionmentioning
confidence: 99%
“…Insects have been identified as the world’s most important pollinators, contributing to 87% of pollination globally, making their services critical for the sustainability of natural ecosystems [ 10 , 11 ]. Camellia oleifera Abel.…”
Section: Introductionmentioning
confidence: 99%
“…2 1:9 = Each third row of 'Hass' has one 'Ettinger' tree for every two 'Hass' trees (11% 'Ettinger', see Figure 2). 3 See Figures 1 and 2.…”
Section: Hive Introductionmentioning
confidence: 99%
“…Insufficient pollination is a major limiting factor for avocado ( Persea americana Mill.) fertility [ 1 , 2 , 3 ]. In Mediterranean regions, and in particular in Israel, the honeybee ( Apis mellifera ; HB) is the main commercial pollinator of avocados.…”
Section: Introductionmentioning
confidence: 99%